Analisis Kesalahan pada Perbandingan Trigonometri untuk Siswa Kelas X Fase E3 SMAK N ST Dominikus Sumba Barat Daya - Kabobu, Kornelis Kura; Lede, Yulius Keremata (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the errors made by Grade X (Phase E3) students at SMAK N St. Dominikus, Southwest Sumba, in solving trigonometry ratio problems, employing a descriptive qualitative method. The research subjects were Grade X (Phase E3) students, with data collected through written tests, interviews, and documentation. Data analysis involved data reduction, data presentation, and conclusion drawing by identifying, categorizing, and describing student errors based on test results and interviews. The findings indicate that the errors included conceptual, procedural, and calculation errors. Conceptual errors were characterized by an inability to understand the relationships between sides in a right-angled triangle and the application of sine, cosine, and tangent. Procedural errors were evident in unsystematic solution steps, while calculation errors stemmed from a lack of precision in arithmetic operations. Interviews revealed that these errors were influenced by a lack of understanding of basic trigonometric concepts, insufficient practice, and low precision in calculations. Overall, the findings suggest that mastering basic concepts is the primary factor that needs to be strengthened to reduce student errors in solving trigonometry problems.